Dukhtar = Daughter [videorecording (DVD)] - Nathaniel, Afia; Mumtaz, Samiya; Aref, Saleha; Mirza, Mohib, 1979- (Silk Road Cinema, 2016)
Allah Rakhi kidnaps her ten-year-old daughter Zainab to save her from a child marriage to a tribal leader. Their escape is a damning loss of honor for the two families, and a deadly hunt begins for them. Desperate for help, Allah Rakhi strikes an unlikely deal with a cynical ex-Mujahid truck driver to take them to Lahore. What follows is an epic journey through the sweeping landscape of Pakistan where the search for freedom and love comes with a price.